Rethinking the Buddha : early Buddhist philosophy as meditative perception - Shulman, Eviatar (Cambridge University Press, 2014)
Shulman traces the development of the four noble truths, which in fact originated as observations to be cultivated during meditation.
Keywords: Meditation -- Buddhism.; Buddhist philosophy.; Buddhism -- Doctrines.; Philosophie bouddhique.; Bouddhisme -- Doctrines.; RELIGION -- Comparative Religion.; Buddhism -- Doctrines; Buddhist philosophy; Meditation -- Buddhism; Buddhismus; Lehre; Meditation